Surface anatomy of the head and neck a clinical correlation - Lingham, Omkara Rubini (Penerbit Universiti Teknologi Mara, 2009)
This book imparts concise information on the surface marking of the head and neck with clinical and radiological correlation. It is aimed principally at medical students starting clinical work but it also provides a sound platform for those in the surgical and inventional specialities of the head and neck.